To kill a shadow - Quinn, Katherine (Author) (Entagled Teen, an imprint of Entangled Publishing LLC, 2023)
"Jude Maddox knows nothing of love or even light. He knows only his grim duty as the Hand of Death, to lead the Knights of the Eternal Star into a land filled with nightmares and certain demise. It's only when he sees her--a young woman with wild, amber eyes who's as fierce, defiant, and swift as the shadow beasts themselves--that he feels the warmth of life in his blood. The other Knights may fear their lethal commander, with his hard, merciless demeanor. Outcast Kiara Frey sees only a leader, a man who knows how to survive. Someone like her. But wanting him is as treacherous as the shadows themselves--and just as seductive"--